Larvae of trap-jaw ants, Odontomachus LATREILLE, 1804 (Hymenoptera: Formicidae): Morphology and biological notes - Fox, Eduardo G. P.; Smith, Adrian A.; Gibson, Joshua C.; Solis, Daniel R. [UNESP] (My University, 2017)
This study aims to contribute to the neglected topic of larval biology in ants. The number of larval instars for three different species of trap-jaw ants, Odontomachus meinerti FOREL, 1905, Odontomachus bauri EMERY, 1892, and Odontomachus brunneus (PATTON, 1894) was estimated to three based on the maximum width frequency distributions of head capsules from worker and male larvae. The obtained number of larval instars was smaller than from a previous report with another species in the genus, indicating possible interspecific variation. Larvae of different sexes and instars among the three different species were generally identical, differing merely by relative dimensions and patterns of hair distribution. Dorsal doorknob protuberances were recorded for the first time in the genus, and observed being used to fix larvae onto nest walls. From observing several individuals, we suggest the ornamentation of spiracle peritremes and the types of body protuberances are useful characters for larval taxonomy within this group. Moreover, a few individuals were found possessing anomalous structures which are reminiscent of characters from related taxa. Finally, some brief observations are made on an unidentified parasite found inside some mature larvae of O. bauri.
Keywords: Ecdysis; Juvenile morphology; O. bauri; O. brunneus; Odontomachus meinerti; Post-embryonic development